Consulting — A Potpourri - Brosseau, John (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper explores the role of consulting in elementary school counseling. Consulting is defined and its various applications in the elementary school are discussed. In particular, consulting with teachers and parents is reviewed, as well as the efficacy of consulting. A consulting model developed by Caplan in the field of mental health is presented as a comprehensive consulting model which may be of use to elementary school counselors.